Narratives and Economic Policy: Theoretical Explorations and the Case of Central~Bank Communication in Brazil - Carsten Herrmann-Pillath; Luís Otávio Bau Macedo (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
Increasingly, economists study narratives and their causal impact on economic processes. This paper proposes a new theoretical framework of narrative analysis that is based on the philosophy of language, especially speech act theory, motivated by the observation that, so far, the economic approaches focus on the representational function of narratives and tend to emphasize negative consequences of biased, distorted, and simplified representation. In contrast, we define narratives as a medium of distributed cognition and mediators of collective agency in networks of agents operating in an uncertain and complex world that is materially constituted by their actions. After sketching the theory, we introduce a case study on the role of central bank communication in recent economic developments in Brazil for illustrative purposes, focusing on the role of financial audiences and a specific narrative genre, the "austerity genre" induced by the Brazilian Central Bank.
Keywords: E71; B41; B52; D80; 330; Financial Sector; Narrative Process Analysis; Speech Act Theory; Audiences; Brazil; Central Bank Communication; Austerity